Kebijakan Penyetaraan Kedudukan Sosial Masyarakat melalui Penghapusan Kelas dalam BPJS Kesehatan - Suryapuspita, Merintha (Jurnal Administrasi Politik dan Sosial, 2024)
BPJS Kesehatan is a national health insurance program in Indonesia managed by the Social Security Administering Agency. The elimination of classes in BPJS Kesehatan is one of the major reform steps in the health insurance system in Indonesia. This study aims to see the perspective of the Policy of Equalizing Social Status of Society through the Elimination of Classes in BPJS Kesehatan. This study uses a normative legal approach method, namely a method that reviews and discusses research objects by emphasizing legal aspects. The data obtained in this study will be analyzed using qualitative analysis methods. Comprehensive and participatory policies will be more effective in achieving the goal of equality. Overall, the policy of eliminating classes in BPJS Kesehatan has the potential to advance the principles of social justice and equal access to health services